Direct Determination of Burgers Vectors of Threading Mixed Dislocations in 4H-SiC c-Plane Wafers Grown by PVT Method. (21st September 2015) - Guo, Jianqiu; Yang, Yu; Wu, Fangzhen; Goue, Ouloide Yannick; Raghothamachar, Balaji; Dudley, Michael
Abstract : A systematic method is developed and demonstrated here to determine the Burgers vectors of threading mixed dislocations in4H-SiC c-plane offcut wafers grown by PVT method. Both Synchrotron Monochromatic X-ray Topography and Ray Tracing Simulations are used in this method. Measurements confirm that in a commercial offcut wafer the majority of the threading dislocations with screw component are actually mixed type dislocations.